SPECIFIC PREVENTION OF BRADSOT’S DISEASE IN SHEEP. - Ergashev, N. B.; Mengliyev, G‘. A. (American Journal of Botany and Bioengineering, 2024)
This article provides information on the main methods of prevention of bradzot disease and the effectiveness of vaccines, the development of optimal methods of quantitative control of the intensity of immunity, and specific prevention of clostridiosis created by scientists from different countries.